Business models on startups: a multicase study - Piñeiro, Fabio da Silva; Oliveira, Janaina Mendes de; Cruz, Anderson Cougo da; Patias, Tiago Zardin (Revista de Administração da UFSM, 2017)
The Business Model Canvas has become a business model heavily used in the initial design of startups that visualize a tool as a troubleshooter. With this, the issues that accompany the implementation process and the execution of the studied model, which strategically direct such startups. The purpose of this study was to verify how companies used and in what form the business model. Three startups were located in the city of Pelotas (RS, Brazil), selected because they exhibit different specificities. It was found that two of the three companies studied used the model in a structured way. However, a startup that achieved a progressive and non-disruptive development was just a startup that did not use Business Model Canvas. This response was published online with reference to initial references that are not contemplated. Finally, it can be considered that the success of the initialization is not directly available with the tool of the tool. <pre style="text-align: justify; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">The Business Model Canvas has become a business model heavily used in the initial design of startups that visualize a tool as a troubleshooter. With this, the issues that accompany the implementation process and the execution of the studied model, which strategically direct such startups. The purpose of this study was to verify how companies used and in what form the business model. Three startups were located in the city of Pelotas (RS, Brazil), selected because they exhibit different specificities. It was found that two of the three companies studied used the model in a structured way. However, a startup that achieved a progressive and non-disruptive development was just a startup that did not use Business Model Canvas. This response was published online with reference to initial references that are not contemplated. Finally, it can be considered that the success of the initialization is not directly available with the tool of the tool.